2011
DOI: 10.1016/j.tox.2011.01.015
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro study of vascular endothelial toxicity of CdTe quantum dots

Abstract: Quantum dots (QDs), as novel bioimaging and drug delivery agents, are generally introduced into vascular system by injection, and thus directly exposed to vascular endothelial cells (ECs). However, the adverse effects of QDs on ECs are poorly understood. In this study, employing human umbilical vein ECs (HUVECs), we investigated the potential vascular endothelial toxicity of mercaptosuccinic acid (MSA)-capped CdTe QDs in vitro. In the experiment, water-soluble and pH stable CdTe QDs were synthesized; and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
72
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(80 citation statements)
references
References 54 publications
(43 reference statements)
6
72
0
1
Order By: Relevance
“…QDs induce the generation of reactive oxygen species, 50 which leads to detrimental autophagic cell death or necrosis [51][52][53] or which activates intrinsic mitochondrial apoptotic pathways. 21 It is known that smaller QDs penetrate deeper into cells and induce toxicity at far quicker rates than their larger counterparts. However, in our studies, QD4.7 was found to be comparatively more cytotoxic than QD2.7, which could be attributed to either the higher negative charge on the surface or to their preferential accumulation in the cytoplasm, thereby triggering different or additional toxicity mechanisms.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…QDs induce the generation of reactive oxygen species, 50 which leads to detrimental autophagic cell death or necrosis [51][52][53] or which activates intrinsic mitochondrial apoptotic pathways. 21 It is known that smaller QDs penetrate deeper into cells and induce toxicity at far quicker rates than their larger counterparts. However, in our studies, QD4.7 was found to be comparatively more cytotoxic than QD2.7, which could be attributed to either the higher negative charge on the surface or to their preferential accumulation in the cytoplasm, thereby triggering different or additional toxicity mechanisms.…”
Section: Figurementioning
confidence: 99%
“…Another class of NPs is presented by semiconductor quantum dots (QDs), which possess unique optoelectronic properties such as tunable narrow emission spectra, high quantum yields, broad absorption spectra, and high resistance to photobleaching. 21 QDs are successfully used in biomedicine as labeling agents for imaging biological molecules, cells, and even tissues 22 or to trace drug molecules in live organisms. 23,24 However, for biological applications, QDs must be surface passivated with other materials to allow for dispersion and to prevent the leakage of toxic heavy metals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated the toxicity of CdTe QDs in mammalian cells [6][7][8] and revealed that this toxicity is dependent on their physicochemical properties, such as size, charge, concentration, and outer coating. 9 It has been suggested that the toxicity of CdTe QDs is related to oxidative stress, which can lead to lysosome enlargement, 8 mitochondrial network fragmentation, 7 and activation of autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…The large surface area exhibited by QDs enables them to be functionalised with biocompatible and specific ligands for site-specific activity [1,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%